2011
DOI: 10.1016/j.sigpro.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

A fractional approach for the motion planning of redundant and hyper-redundant manipulators

Abstract: The trajectory planning of redundant robots through the pseudoinverse control leads to undesirable drift in the joint space. This paper presents a new technique to solve the inverse kinematics problem of redundant manipulators, which uses a fractional differential of order a to control the joint positions. Two performance measures are defined to examine the strength and weakness of the proposed method. The positional error index measures the precision of the manipulator's end-effector at the target position.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In addition, only the PA10 end-effector position is considered in the simulations. Table 1 presents the joint-physical limits of this manipulator, and the coefficients involved in (13) are set as ϑ = 0.1 and κ p = κ v = 25. The feedback gains involved in (8) are set as α = β = 1.75.…”
Section: Simulation Comparison and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, only the PA10 end-effector position is considered in the simulations. Table 1 presents the joint-physical limits of this manipulator, and the coefficients involved in (13) are set as ϑ = 0.1 and κ p = κ v = 25. The feedback gains involved in (8) are set as α = β = 1.75.…”
Section: Simulation Comparison and Validationmentioning
confidence: 99%
“…For example, in [11], an obstacle-avoidance scheme with Jacobian transpose for redundant manipulators is presented. In [13], a pseudoinverse-based scheme with multi-objective achievement for avoiding obstacle is investigated. In [15], an obstacle-avoidance scheme with noise tolerance for redundant manipulators is developed.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above formulations, the pseudoinversetype technique is depicted in an analytical-solution form, and it can thus solve the redundancy resolution problem readily. This significant characteristic has popularized the research and application of the pseudoinverse-type technique in the past decades [1], [2], [14], [15], [17], [19], [21]- [23], [32]- [36].…”
Section: A Robotic Redundancy Resolutionmentioning
confidence: 99%
“…This technique is a powerful alternative for the kinematic control of redundant robot manipulators. By exploiting the pseudoinverse-type technique, many studies have been reported on redundant robot manipulators [14], [15], [17], [19], [21]- [27].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been presented to solve the obstacle avoidance issue for redundant manipulators. Among these works, the first group of works involves the use of Jacobian pseudo-inverse [10,11,12,13,14,15]. In this kind of method, the inverse kinematics solution of manipulators is expressed as a sum of a minimum-norm special solution and a general solution that contains an arbitrary vector.…”
Section: Introductionmentioning
confidence: 99%